Identification of novel biomarker candidates for hypertrophic cardiomyopathy and other cardiovascular diseases leading to heart failure - Rehulkova, H; Rehulka, P; Myslivcova Fucikova, A; Stulik, J; Pudil, R (Physiological research, 2016)
In-depth proteome discovery analysis represents new strategy in an effort to identify novel reliable specific protein markers for hypertrophic cardiomyopathy and other life threatening cardiovascular diseases. To systematically identify novel protein biomarkers of cardiovascular diseases with high mortality we employed an isobaric tag for relative and absolute quantitation (iTRAQ) proteome technology to make comparative analysis of plasma samples obtained from patients suffering from non-obstructive hypertrophic cardiomyopathy, stable dilated cardiomyopathy, aortic valve stenosis, chronic stable coronary artery disease and stable arterial hypertension. We found 128 plasma proteins whose abundances were uniquely regulated among the analyzed cardiovascular pathologies. 49 of them have not been described yet. Additionally, application of statistical exploratory analyses of the measured protein profiles indicated the relationship in pathophysiology of the examined cardiovascular pathologies.
Keywords: Male; biologické markery; srdeční selhání; Biomarkers; Cardiomyopathy, Hypertrophic; proteom; Adult; Aged; dospělí; Case-Control Studies; mužské pohlaví; senioři; proteomika; senioři nad 80 let; lidé; ženské pohlaví; studie případů a kontrol; Heart Failure; Humans; Aged, 80 and over; hypertrofická kardiomyopatie; Proteomics; Female; Proteome; lidé středního věku; Middle Aged